Analiza učinkovitosti izdatkov za raziskave in razvoj - Lautar, Katja (Naše gospodarstvo, 2011)
This contribution examines previous findings that Slovenia belongs among the less effective EU member states based on an examination of the efficiency of R&D spending. Using the average amount of R&D spending (in % GDP), Slovenia falls below average performance. In countries with efficient R&D spending, better institutional support for research and development and innovation activities (e.g., for the degree of protection of intellectual property, human resources employment share in natural sciences and engineering, relative high-specialization of the economy, coordination of policies and measures in the various fields) confirmed the usefulness of accelerated R&D spending, which in the long run has been shown in the higher economic growth and higher productivity. DEA analysis calculated the relative efficiency for each of the parameters of the R&D spending for each country as well as the indicative proposals for improvements (either the reduction of inputs in order to achieve the same direct effect or output or vice versa, given the contributions of what should be the direct effect output that the country is to be effective). The current situation in Slovenia in the field of indicators related to the R&D is summarized. Using the nonparametric method, we reaffirm the conclusions on the efficiency of R&D spending in Slovenia. The results of the analysis indicate that Slovenia is relatively very inefficient in terms of R&D spending, innovation, and technology (the calculations of relative efficiency range from 30% to 60%).
Keywords: podjetja; raziskave; razvoj; inovacije; investicije; stroški; učinkovitost; efficiency; vrednotenje